1996
DOI: 10.1016/0042-6989(95)00313-4
|View full text |Cite
|
Sign up to set email alerts
|

Neural encoding of binocular disparity: Energy models, position shifts and phase shifts

Abstract: Neurophysiological data support two models for the disparity selectivity of binocular simple and complex cells in primary visual cortex. These involve binocular combinations of monocular receptive fields that are shifted in retinal position (the position-shift model) or in phase (the phase-shift model) between the two eyes. This article presents a formal description and analysis of a binocular energy model with these forms of disparity selectivity. We propose how one might measure the relative contributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
346
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(356 citation statements)
references
References 57 publications
7
346
3
Order By: Relevance
“…The geometric mean of the pooling ratio amounted to 1.80 for the Y direction and 1.30 for the X direction for our sample of complex cells. Sasaki and Ohzawa (2007) reported that the majority of complex cells in the early visual cortex pool subunits minimally in space to make up the monocular RFs (median of size ratio, ϳ1.21 in area), concluding that complex cells can be described adequately by the standard energy model without spatial pooling (Adelson and Bergen, 1985;Qian 1994;Fleet et al, 1996). An apparent contradiction with this report can be explained by a difference in the metric for evaluating the degree of spatial pooling.…”
Section: Spatial Pooling Of Binocular Disparity Detectorscontrasting
confidence: 49%
“…The geometric mean of the pooling ratio amounted to 1.80 for the Y direction and 1.30 for the X direction for our sample of complex cells. Sasaki and Ohzawa (2007) reported that the majority of complex cells in the early visual cortex pool subunits minimally in space to make up the monocular RFs (median of size ratio, ϳ1.21 in area), concluding that complex cells can be described adequately by the standard energy model without spatial pooling (Adelson and Bergen, 1985;Qian 1994;Fleet et al, 1996). An apparent contradiction with this report can be explained by a difference in the metric for evaluating the degree of spatial pooling.…”
Section: Spatial Pooling Of Binocular Disparity Detectorscontrasting
confidence: 49%
“…Having said that, we assumed that the structure‐function relationship would be influenced by the presence of MSON 2, 14. Because of the balanced signal requirements for human binocular vision,15 it was assumed that the structural‐functional relationships would be influenced differently by unbalanced signaling (unilateral MSON, with the better/dominant eye providing most of the information) from the eye to the visual cortex, compared to either bilateral symmetrically reduced signaling (bilateral MSON) or bilateral normal signaling (bilateral MSNON). To test this hypothesis, we investigated patients with MS who (1) never suffered from MSON (MSNON), (2) suffered from unilateral MSON or (3) bilateral MSON.…”
Section: Introductionmentioning
confidence: 99%
“…Recent models describe binocular matching in terms of spatial filtering (Ohzawa et al, 1990;Fleet et al, 1996;Cumming and Parker, 1997;Qian and Zhu, 1997;Anzai et al, 1999), so in that framework, solving the matching problem is tantamount to finding similar filter outputs from the two eyes. For the outputs of matched filters to be similar, their inputs must be similar, so binocular matching in this scheme requires similar local intensity patterns in the left and right retinal images.…”
Section: Effect Of Disparity Gradientmentioning
confidence: 99%